Using Aggregate Vasoactive-Inotrope Scores to Predict Clinical Outcomes in Pediatric Sepsis - Shah, Palak; Petersen, Tara L.; Zhang, Liyun; Yan, Ke; Thompson, Nathan E. (Frontiers in Pediatrics, 2022)
Objectives The heterogeneity of sepsis makes it difficult to predict outcomes using existing severity of illness tools. The vasoactive-inotrope score (VIS) is a quantitative measure of the amount of vasoactive support required by patients. We sought to determine if a higher aggregate VIS over the first 96 h of vasoactive medication initiation is associated with increased resource utilization and worsened clinical outcomes in pediatric patients with severe sepsis. Design Retrospective cohort study. Setting Single-center at Children's Wisconsin in Milwaukee, WI. Patients One hundred ninety-nine pediatric patients, age less than 18 years old, diagnosed with severe sepsis, receiving vasoactive medications between January 2017 and July 2019. Interventions Retrospective data obtained from the electronic medical record, calculating VIS at 2 h intervals from 0–12 h and at 4 h intervals from 12–96 h from Time 0. Measurements Aggregate VIS derived from the hourly VIS area under the curve (AUC) calculation based on the trapezoidal rule. Data were analyzed using Pearson's correlations, Mann-Whitney test, Wilcoxon signed rank test, and classification, and regression tree (CART) analyses. Main Results Higher aggregate VIS is associated with longer hospital LOS (p < 0.0001), PICU LOS (p < 0.0001), MV days (p = 0.018), increased in-hospital mortality (p < 0.0001), in-hospital cardiac arrest (p = 0.006), need for ECMO (p < 0.0001), and need for CRRT (p < 0.0001). CART analyses found that aggregate VIS >20 is an independent predictor for in-hospital mortality (p < 0.0001) and aggregate VIS >16 for ECMO use (p < 0.0001). Conclusions There is a statistically significant association between aggregate VIS and many clinical outcomes, allowing clinicians to utilize aggregate VIS as a physiologic indicator to more accurately predict disease severity/trajectory in pediatric sepsis.